LEED for Homes: Explanation of the Landscape Irrigation Budget Calculation for Florida - Michael D. Dukes (EDIS)
AE441, a 3-page fact sheet by Michael D. Dukes, explains the landscape irrigation budget found under “Landscaping” in the LEED for Homes Rating System. Published by the UF Department of Agricultural and Biological Engineering, January 2009. Revised February 2015. Deaccessioned from Ask IFAS August 2021.